Just Policing and Mercy: Capturing the Ethical Dimension of Deadly Force Assessments - Reinhardt, Daniel (Journal of sociology and Christianity, 2023)
The Graham v. Connor Supreme Court decision is a foundational ruling concerning police force. While strongly supported by law enforcement practitioners, some scholars question its viability as a prudent guideline for humane societies. This article will consider this dispute between police scholars and practitioners concerning the viability of Graham v. Connor from a just war perspective. The just war tradition has not only promoted restraint in war but has also influenced policing. However, even though the just war tradition has offered some level of ethical influence on the humane application of force in policing, Graham v. Connor appears to deemphasize the ethical weight of deadly force decisions and can lead to inhumane force applications. To mitigate this problem, this article will continue to draw from the just war tradition through a focus on the emphasis on mercy in the early Christian just war tradition. The appropriation of mercy as a clear and applicable part of a formal guideline for deadly force can usher officers back to the ethical dimension of decision making to protect life; it can enable police leaders, force assessment boards, prosecutors, and courts to assess the actions of officers judiciously and promote societal peace.